MICROBIAL FLORA OF THE GASTRO-INTESTINAL TRACT OF NILE TILAPIA (Oreochromis niloticus) CAUGHT FROM RIVER DANDARU, IBADAN - JIMOH, W.A.; OLADELE-BUKOLA , M.O.; ADEBAYO, M.D.; YUSUFF, A.A.; AZEEZ, A.F.; SALAMI, O.O. (Nigerian Journal of Fisheries, 2013)
The study reports the microbial load and diversity in the gastro-intestinal tract of Nile Tilapia Oreochromis niloticus caught in River Dandaru, Ibadan. A set of adult samples of Nile Tilapia was caught from the river Dandaru, Ibadan. Microbial loads and characterization of micro organisms present in the gut region of the captured Clarias gariepinus were examined using standard microbiological procedures. The isolated fungi isolated were Geotricum candidum, Aspergillus candidus, Penicillium expansum while the bacteria isolated were Proteus mirabilis, Bacillus licheniformis, Pseudomonas aeruginosa, Bacillus megaterium, Staphylococcus aureus, Flavobacterium aquatile, Pseudomonas cepacia, Lactobacillus brevis. The microbial count of Nile Tilapia caught from river Dandaru Ibadan were; the total plate count was 3.3 x 106 CFUs/g, total coliform count was 2.4 x104 CFUs/g, total anaerobic count was 1.0 x 103 CFUs/g, total faecal coliform count was 1.1 x 103 CFU/ml, total fungi count was 7.5 x 103 spore/g.